2015
DOI: 10.1159/000430095
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Molecular Events during the Maturation of the Developing Mouse Prefrontal Cortex

Abstract: Recent progress in psychiatric research has accumulated many mouse models relevant to developmental neuropsychiatric disorders using numerous genetic and environmental manipulations. Since the prefrontal cortex (PFC) is essential for cognitive functions whose impairments are central symptoms associated with the disorders in humans, it has become crucial to clarify altered developmental processes of PFC circuits in these mice. To that end, we aimed to understand a sequence of molecular events during normal mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 78 publications
(70 reference statements)
0
23
0
Order By: Relevance
“…We have begun to clarify these by characterizing a sequence of gene expression patterns during mouse PFC development (Ueda et al, 2015, and Figure 3). The study showed that the developmental processes of PFC proceed sequentially, and interneuron maturation and myelination take place relatively later in the maturation (by postnatal day 35), supporting the idea that myelination is correlated with local circuitry maturation.…”
Section: Neurobiological Framework For Cognitive Function: Pfcmentioning
confidence: 99%
See 4 more Smart Citations
“…We have begun to clarify these by characterizing a sequence of gene expression patterns during mouse PFC development (Ueda et al, 2015, and Figure 3). The study showed that the developmental processes of PFC proceed sequentially, and interneuron maturation and myelination take place relatively later in the maturation (by postnatal day 35), supporting the idea that myelination is correlated with local circuitry maturation.…”
Section: Neurobiological Framework For Cognitive Function: Pfcmentioning
confidence: 99%
“…The study showed that the developmental processes of PFC proceed sequentially, and interneuron maturation and myelination take place relatively later in the maturation (by postnatal day 35), supporting the idea that myelination is correlated with local circuitry maturation. But even after postnatal day 35, the circuitry is still immature and continues to further maturate during adolescence (based on the responsiveness to MK801 injection measured by microdialysis, at postnatal day 42, the PFC does not show the adult like response which is observed at postnatal day 56)(Ueda et al, 2015). The maturation of PFC circuitry is slower than in any other brain regions (e.g., Teffer et al, 2013; Ueda et al, 2015).…”
Section: Neurobiological Framework For Cognitive Function: Pfcmentioning
confidence: 99%
See 3 more Smart Citations